Interval prediction of order statistics and record values using concomitants of order statistics and record values for Morgenstern family of distributions (Journal of Statistical Research, 2023)
In this paper, we discuss the problem of predicting intervals for future order statistics and k-record values based on observed concomitants of order statistics and observed concomitants of k-record values arising from a Morgenstern family of distributions. The coverage probabilities obtained are accurate and independent of the parent distribution. A real data set is also considered to exemplify the proposed methodologies developed in this paper.Journal of Statistical Research 2022, Vol. 56, No. 1, pp. 55-72